2009
DOI: 10.1163/156854008x400612
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Farfantepenaeus Aztecus Postlarvae in Three Lagoon-System Inlets in the Southwestern Gulf of Mexico

Abstract: This study evaluates the night-time recruitment of Farfantepenaeus aztecus postlarvae and its relation with temperature, salinity, and velocity and flow direction of the current in the artificial inlet of the Camaronera lagoon of Alvarado, Veracruz, the Soto la Marina river inlet of Tamaulipas, and the Puerto Real inlet of Términos lagoon, Campeche. Sampling was done during the night. A conical 243 μm mesh net was used for capture. The total catch of F. aztecus for the three coastal systems was 95,279 postlarv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The strong flow of freshwater in high rainfall years generates a physical barrier preventing the entrance of oceanic water and therefore the pink shrimp into the estuary (Möller et al, 2009;Pereira and D'Incao, 2012). The same pattern of greater post-larvae abundance related to the flow of ocean water into the adjacent coastal systems and the entry of post-larvae shrimp into the estuary can be observed for other penaeids, such as Farfantepenaeus subtilis (Pérez Farfante, 1967) and F. aztecus (Ives, 1891) (Lhomme, 1992;Cházaro-Olvera et al, 2009). The greater abundance of post-larvae in SM, evidenced by PL2 model, may be due to the proximity of this inlet to the estuary connection with the ocean and also indicate the importance of shallow inlets in the lower estuary to the arrival and settlement of pink shrimp.…”
Section: Post-larvae and Pink Shrimp Juveniles: Inlets And Salinity Imentioning
confidence: 79%
See 1 more Smart Citation
“…The strong flow of freshwater in high rainfall years generates a physical barrier preventing the entrance of oceanic water and therefore the pink shrimp into the estuary (Möller et al, 2009;Pereira and D'Incao, 2012). The same pattern of greater post-larvae abundance related to the flow of ocean water into the adjacent coastal systems and the entry of post-larvae shrimp into the estuary can be observed for other penaeids, such as Farfantepenaeus subtilis (Pérez Farfante, 1967) and F. aztecus (Ives, 1891) (Lhomme, 1992;Cházaro-Olvera et al, 2009). The greater abundance of post-larvae in SM, evidenced by PL2 model, may be due to the proximity of this inlet to the estuary connection with the ocean and also indicate the importance of shallow inlets in the lower estuary to the arrival and settlement of pink shrimp.…”
Section: Post-larvae and Pink Shrimp Juveniles: Inlets And Salinity Imentioning
confidence: 79%
“…The entry of these organisms into estuaries follows the patterns observed in other species of penaeids and also blue crabs from other coastal regions (D'Incao, 1991;Lhomme, 1992;Bulger et al, 1995;Epifanio, 2007;Cházaro-Olvera et al, 2009). These species are considered important the abundance of juveniles and to fisheries production (D'Incao, 1991;Costa et al, 2008;Möller et al, 2009;Pereira and D'Incao, 2012).…”
Section: Introductionmentioning
confidence: 74%
“…Staples (1980) observed that post-larvae of F. merguiensis moved from the substrate to the water column and migrated up the estuary by the influence of tidal flooding (of salt water). The same behaviour was observed for F. aztecus in their migration to estuaries in the Gulf of Mexico (Cházaro-Olvera et al ., 2009). It can be concluded that if conditions are favourable, and salt water entry intense, a favourable scenario is created for the migration of post-larvae into the Lagoa dos Patos estuary.…”
Section: Discussionmentioning
confidence: 99%
“…The high abundance of post-larvae, at U1–U4 and P1 and P5, indicate the importance of these sites for pink shrimp recruitment, because they may represent a nesting area for individuals of ocean origin. The search for a substrate in marginal areas of the unprotected central area (mainly represented by U2) and shallow waters in protected areas at the mouth of the estuary as soon as they enter estuaries, may represent the attempt of post-larvae to remain in this environment, thus preventing the ebb tide from carrying them back to the ocean, as demonstrated for F. merguiensis , F. aztecus and Melicertus plebejus (Young & Carpenter, 1977; Adnan et al ., 2002; Cházaro-Olvera et al ., 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation